Transformational Leadership in Green Human Resource Management Practice: A Systematic Literature Review - Fitri, Sari; Hidayat, Rahmad; Yuliani, Tri (Airlangga Journal of Innovation Management, 2025)
This article aims to examine the role of transformational leadership in the implementation of Green Human Resource Management (Green HRM) and its contribution to organizational environmental sustainability. The urgency of this study lies in the growing demand for organizations to integrate sustainability principles into their human resource practices. Using a Systematic Literature Review (SLR) approach, 11 articles were screened and analyzed from reputable databases, including Scopus and ScienceDirect. The findings reveal that Green HRM encompasses recruitment, training, performance management, and compensation processes that are grounded in environmentally friendly values. However, its successful implementation is significantly influenced by transformational leadership. Transformational leaders play a pivotal role in shaping pro-environmental organizational culture, motivating employees to adopt green behaviors, and ultimately enhancing environmental performance and long-term sustainability. In addition, the study highlights that the effectiveness of Green HRM implementation is not solely determined by internal leadership, but also by external factors such as government policy support, stakeholder engagement, and collective awareness of environmental issues. This study concludes that the integration of Green HRM and transformational leadership represents a key strategic approach to building competitive, sustainable organizations. Theoretically, it contributes to the growing body of literature on leadership and sustainable HR practices. At the same time, practically, it provides guidance for managers and policymakers to align leadership styles with green initiatives to achieve long-term environmental goals.